2019
DOI: 10.1101/845917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular epidemiology of Escherichia coli producing CTX-M and plasmid AmpC-type β-lactamases from dairy farms identifies a dominant plasmid encoding CTX-M-32 but no evidence for transmission to humans in the same geographical region

Abstract: ObjectivesThe objective of this study was to identify the mechanisms of cefotaxime resistance (CTX-R) in 1226 Escherichia coli from 4581 environmental samples collected on 53 dairy farms over a 2-year period in South West England and to characterise a blaCTX-M-32-producing plasmid, pMOO-32, found to be widely distributed.MethodsCTX-R isolates were identified using MIC breakpoint agar plates. β-lactamase genes of interest (GOIs) were detected by PCR. WGS was performed and analysed using the Center for Genomic E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Confirmation of AmpC hyper-production and identification of porin loss and marR mutations in E. coli from dairy farms Our first aim was to investigate putative AmpC hyper-producing E. coli isolates from dairy farms identified in our recent surveillance study. 10,11 We decided to focus on a 50 x 50 km subregion of the study area, in which 25 farms were found to be positive for putative AmpC hyperproducers: defined as cefotaxime-resistant isolates that were PCR-negative for known mobile cephalosporinase genes. First, antibiograms were determined for one putative AmpC hyperproducing isolate from each of 4 randomly selected farms.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Confirmation of AmpC hyper-production and identification of porin loss and marR mutations in E. coli from dairy farms Our first aim was to investigate putative AmpC hyper-producing E. coli isolates from dairy farms identified in our recent surveillance study. 10,11 We decided to focus on a 50 x 50 km subregion of the study area, in which 25 farms were found to be positive for putative AmpC hyperproducers: defined as cefotaxime-resistant isolates that were PCR-negative for known mobile cephalosporinase genes. First, antibiograms were determined for one putative AmpC hyperproducing isolate from each of 4 randomly selected farms.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five test E. coli isolates came from dairy farms located within a 50 x 50 km region of the South West of England, part of the wider area of our earlier study. 10,11 Isolates came, variously, from faecally contaminated sites around calves, heifers, cows and the near-farm environment. Samples were collected between January 2017 and December 2018.…”
Section: Bacterial Isolates Identification and Susceptibility Testingmentioning
confidence: 99%
See 3 more Smart Citations